2021
DOI: 10.1111/jfbc.13938
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of hesperidin on streptozotocin‐diabetes mellitus‐induced testicular DNA damage and sperm quality degradation in Sprague–Dawley rats

Abstract: This study aimed to investigate the effect of hesperidin on reproductive damage caused by diabetes mellitus. A total of 24 adult male rats were divided into four groups: control group, hesperidin group, diabetes mellitus group, and diabetes mellitus + hesperidin group. The study was conducted for 4 weeks. At the end of the study, the rats were sacrificed and testicular oxidative stress markers (MDA, GSH, How to cite this article: Aksu, E. H., Kandemir, F. M., & Küçükler, S. (2021). Ameliorative effect of hespe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Chronic insulin deficiency leads to the breakdown of fats and structural proteins as substitutes for carbohydrates as an energy source, resulting to organ and body weight loss (Abdel‐Mageid, Abou‐Salem, Salaam, & El‐Garhy, 2018). Our findings showed that diabetic rats had a significant reduction in body and testis weight that are consistent with other experiments (Aksu, Kandemir, & Küçükler, 2021; Makinde, Radenahmad, Adekoya, & Olatunji, 2020). However, restoring blood glucose closer to control level and improving the body and testis weight of animals treated with plants, especially with the combination form, revealed an improvement in metabolic status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Chronic insulin deficiency leads to the breakdown of fats and structural proteins as substitutes for carbohydrates as an energy source, resulting to organ and body weight loss (Abdel‐Mageid, Abou‐Salem, Salaam, & El‐Garhy, 2018). Our findings showed that diabetic rats had a significant reduction in body and testis weight that are consistent with other experiments (Aksu, Kandemir, & Küçükler, 2021; Makinde, Radenahmad, Adekoya, & Olatunji, 2020). However, restoring blood glucose closer to control level and improving the body and testis weight of animals treated with plants, especially with the combination form, revealed an improvement in metabolic status.…”
Section: Discussionsupporting
confidence: 92%
“…GPx uses GSH as an electron source to reduce H 2 O 2 into water (Aitken & Roman, 2009). Our results illustrated that CAT and GPx activity were substantially reduced in the diabetic group, as confirmed by another study (Aksu et al, 2021;Nna et al, 2019). Also, in diabetic rats, GSSG increased, and GSH decreased significantly, which is consistent with previous studies (Adedara et al, 2019;Zhou, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Flavonoids, which are secondary metabolites of plants, are phenolic compounds found in almost all vegetables and fruits 18–21 . Flavonoids are compounds with various biological and pharmacological properties, including anti‐allergic, vasodilator, anti‐inflammatory, antiapoptotic, antioxidant, and antithrombotic 22–24 . Quercetin ([3,3′,4′,5,7‐pentahydroxyflavone], QUE) is widely found in vegetables and fruits such as broccoli, strawberries, onions, coriander and apples 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Flavonoids are compounds with various biological and pharmacological properties, including anti-allergic, vasodilator, anti-inflammatory, antiapoptotic, antioxidant, and antithrombotic. [22][23][24] Quercetin ([3,3 0 ,4 0 ,5,7-pentahydroxyflavone], QUE) is widely found in vegetables and fruits such as broccoli, strawberries, onions, coriander and apples. 25,26 It has taken significant attention among researchers in recent years due to its features like cytoprotective, anti-nociceptive, antioxidant, antithrombotic, anti-carcinogenic and anti-inflammatory properties.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that metabolic syndrome reduces the total plasma testosterone levels, which in turn impairs sperm production and motility after 12 weeks of a high-fat diet [ 25 ]. Moreover, diabetes significantly affects several sperm parameters, including increased testicular DNA damage and sperm degradation due to alternations in glucose transport and increased oxidative stress [ 26 , 27 ]. In diabetic men, hyperglycemia increases oxidative stress, a common pathology seen in approximately 50% of all infertile men, thereby causing infertility [ 28 ].…”
Section: Discussionmentioning
confidence: 99%